Herbicide toxicity, selectivity and hormesis of nicosulfuron on 10 Trichogrammatidae (Hymenoptera) species parasitizing Anagasta ( = Ephestia) kuehniella (Lepidoptera: Pyralidae) eggs. Issue 1 (2nd January 2017) - Leite, Germano L. D.; de Paulo, Paula D.; Zanuncio, José C.; Tavares, Wagner De S.; Alvarenga, Anarelly C.; Dourado, Luan R.; Bispo, Edilson P. R.; Soares, Marcus A.
ABSTRACT: Selective agrochemicals including herbicides that do not affect non-target organisms such as natural enemies are important in the integrated pest management (IPM) programs. The aim of this study was to evaluate the herbicide toxicity, selectivity and hormesis of nicosulfuron, recommended for the corn Zea mays L. (Poaceae) crop, on 10 Trichogrammatidae (Hymenoptera) species. A female of each Trichogramma spp. or Trichogrammatoidea annulata De Santis, 1972 was individually placed in plastic test tubes (no choice) with a cardboard containing 45 flour moth Anagasta ( = Ephestia) kuehniella Zeller, 1879 (Lepidoptera: Pyralidae) eggs. Parasitism by these natural enemies was allowed for 48 h and the cardboards were sprayed with the herbicide nicosulfuron at 1.50 L.ha −1, along with the control (only distilled water). Nicosulfuron reduced the emergence rate of Trichogramma bruni Nagaraja, 1983 females, but increased that of Trichogramma pretiosum Riley, 1879, Trichogramma acacioi Brun, Moraes and Smith, 1984 and T. annulata females. Conversely, this herbicide increased the emergence rate of Trichogramma brasiliensis Ashmead, 1904, T. bruni, Trichogramma galloi Zucchi, 1988 and Trichogramma soaresi Nagaraja, 1983 males and decreased those of T. acacioi, Trichogramma atopovilia Oatman and Platner, 1983 and T. pretiosum males. In addition, nicosulfuron reduced the sex ratio of T. galloi, Trichogramma bennetti Nagaraja and Nagarkatti, 1973 and T. pretiosum and increased that of T. acacioi, T. bruni, T. annulata, Trichogramma demoraesi Nagaraja, 1983, T. soaresi and T. brasiliensis . The herbicide nicosulfuron was "harmless" (class 1, <30% reduction) for females and the sex ratio of all Trichogrammatidae species based on the International Organization for Biological Control (IOBC) classification. The possible hormesis effect of nicosulfuron on Trichogrammatidae species and on the bacterium Wolbachia sp. (Rickettsiales: Rickettsiaceae) was also discussed.